2013
DOI: 10.1080/07060661.2013.828100
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity ofPlum pox virus: strains, disease and related challenges for control

Abstract: Plum pox virus (PPV), a member of the genus Potyvirus, family Potyviridae, is a positive-sense single-stranded RNA virus. RNA viruses tend to be genetically diverse because the viral RNA-dependent RNA polymerase responsible for virus replication lacks proofreading capacity. Consequently, PPV is genetically diverse, and nine strains of the virus (D, M, EA, C, Rec, W, T, CR, and An) have been identified to date. At least two of these strains (Rec, T) are the direct products of recombination events, a contributor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 68 publications
(121 reference statements)
1
27
0
Order By: Relevance
“…These results indicate that all the isolates tested belong to the PPV-D strain. The PPV-D strain is widespread in Europe and probably is the most distributed in the world (Maejima et al, 2011;James et al, 2013;Garcia et al, 2014). The origin of the PPV-D isolates in Crimea as well as their phylogenetic relationships has to be elucidated yet.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that all the isolates tested belong to the PPV-D strain. The PPV-D strain is widespread in Europe and probably is the most distributed in the world (Maejima et al, 2011;James et al, 2013;Garcia et al, 2014). The origin of the PPV-D isolates in Crimea as well as their phylogenetic relationships has to be elucidated yet.…”
Section: Resultsmentioning
confidence: 99%
“…Because some strains possess distinct biological properties, such as host preference, aphid transmissibility, disease symptomatology, and geographic distribution (James et al , ; Rimbaud et al , ; Sihelská et al ., ), strain typing has been the sole approach to the characterization of PPV isolates or populations of interest (EPPO, ; IPPC, ). Meanwhile, biological variation among isolates or populations in a single strain has been recognized as another important but unsolved aspect of PPV epidemiology (Candresse and Cambra, ; James et al , ; García et al , ; Rimbaud et al , ). Several studies have revealed intra‐strain variation in biological properties, such as host preference (Maiss et al , ; Dallot et al , ), aphid transmissibility (Deborre et al ., ; Glasa et al , ; Schneider et al , ), and competitiveness (Glasa et al , ), among PPV isolates.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analysis indicates the common ancestor for W, C and СR strains, and this branch further evolved, mainly or exclusively, in the territory of contemporary Russia. Assumptions of East-Europe ancestry of W and С strains have been reported [13,40,53]. A presumable ancestor could appear in Russia or be introduced from Front and Middle Asia with infected plants.…”
Section: Fig 2 Dendrogram Of Plum Pox Virus (Ppv)mentioning
confidence: 99%
“…These are Dideron (D), Marcus (M), Recombinant (Rec), Cherry (С), Cherry Russian (CR), El Amar (EA), Winona (W), Turkish (T) and Ancestral (An) [9,13], clustered into monophylic groups of closely related isolates. Recombination plays important role in the PPV evolution together with spot mutations.…”
Section: Fig 2 Dendrogram Of Plum Pox Virus (Ppv)mentioning
confidence: 99%
See 1 more Smart Citation